Development of Five-Tier Instruments to Identify Students' Misconceptions about Centripetal and Centrifugal Force - Widia, Widia Dina Oktavia (Indonesian Journal of Science and Education, 2023)
The purpose of the study was to determine the development process and the feasibility of a five-tier diagnostic test instrument to identify students' misconceptions about centripetal and centrifugal forces. This research is a type of Research and Development (R&D) with the development model used, namely the 4D (Four-D) development model. This study uses the R&D method because the results of this study are in the form of a diagnostic test instrument to identify misconceptions in the learning process, and to find out the main source of the causes of misconceptions. The results of the diagnostic test of students who have misconceptions about centripetal and centrifugal forces are 20.31%.The percentage of false positive is 9.62%, the false negative is 8.49 and the Lack of Knowledge is 16.97%. From the percentage results obtained that the false positive (FP) and false negative (FN) values ​​are valid because <10%.The results of the validity test on the instrument are said to be valid because >0.3 and the results of the reliability test are Cronbach's Alpha value obtained at 0.715 from 7 item questions. So this instrument can be said to be reliable because the Cronbach's Alpha value is classified as high based on the reliability criteria.